2005
DOI: 10.1016/j.orthres.2004.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Uncemented short‐length diaphyseal segmental replacement prosthesis fixation—Finite element analysis and long‐term results

Abstract: Introduction: Extensively porous coated segmental replacement prostheses with intramedullary cementless fixation to bone over the whole length of stem often exhibit resorption of the surrounding bone due to stress-shielding. This makes them particularly susceptible to aseptic loosening.Study: A finite element analysis of the state of loading of a short-length fixation in a new prosthetic stem design has shown a definite advantage over long-length fixation. The stress pattern within the bone surrounding the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…As seen in sheep radiographs (Fig 4, Animal A), distal loading and distal fit that avoids complete proximal fill of the medullary canal should be considered an essential element of design and is necessary for conservation and preservation of host bone. This observation is also supported by the previous reports of various clinically implemented endoprosthesis designs [3739]. In one study, Werner and his co-authors concluded that a partially coated prosthesis with short segmental distal intramedullary fixation ensured more physiologically adaptive remodeling compared to the fully coated endoprosthesis systems.…”
Section: Discussionsupporting
confidence: 68%
“…As seen in sheep radiographs (Fig 4, Animal A), distal loading and distal fit that avoids complete proximal fill of the medullary canal should be considered an essential element of design and is necessary for conservation and preservation of host bone. This observation is also supported by the previous reports of various clinically implemented endoprosthesis designs [3739]. In one study, Werner and his co-authors concluded that a partially coated prosthesis with short segmental distal intramedullary fixation ensured more physiologically adaptive remodeling compared to the fully coated endoprosthesis systems.…”
Section: Discussionsupporting
confidence: 68%
“…This stress shielding effect results in bone resorption significantly affecting the long‐term performance of the implants 3. Finite element modeling (FEM) has shown that both the strength and Young's modulus of a metal may be controlled by its porosity 6–8. It ought, therefore, to be possible to match the strength and elastic modulus of bone by using porous titanium implants.…”
Section: Introductionmentioning
confidence: 99%
“…Extensively coated femoral stems, such as the FCE, will have a more pronounced bone loss than proximally or partially coated stems (Bobyn et al 1992, Blunn et al 2000, Yamaguchi et al 2000, Werner et al 2005). …”
Section: Discussionmentioning
confidence: 99%